Knowing God - Packer, James Innell, 1926- (London, UK : Hodder and Stoughton, 1973)
Includes scripture index.
The study of God -- The people who know their God -- Knowing and being known -- The only true God -- God incarnate -- He shall testify -- God unchanging -- The majesty of God -- God only wise -- God's wisdom and ours -- Thy word is truth -- The love of God -- The grace of God -- God the judge -- The wrath of God -- Goodness and severity -- The jealous God -- The heart of the gospel -- Sons of God -- Thou our guide -- These inward trials -- The adequacy of God.
Copy 2 donated by Pieter Dijkstal, 5/2003.
Keywords: God -- attributes